Using of Some Inorganic Additives as Flame Retardants for Some Polymers; a Comparison Study - Ugal, Jalil R (Al-Nahrain Journal of Science, 2018)
Five additives were used as flame retardants for epoxy and unsaturated polyester resins which are: Tetraethyl ammonium bromodichloro phenyl phosphonate, (C2H5)4N[PhPCl2Br] (I), Ammonium phosphate (II), Borax (III), Chlorinated paraffine (IV) and a mixture of additives (I+IV) in the mole ratio (1:1) (V) to study their synergetic effect. The compounds, tetraethyl ammonium bromodichloro phenyl antimonate (C2H5)4N[PhSbCl2Br] and tetraethyl ammonium chlorodibromo phenylantimonate(C2H5)4N[PhSbBr2Cl] were used as flame retardantsfor polyethylene (Low density and high density ) and polypropylene. These additives were used in different percentages(0-10%) and the samples of polymers were prepared in the dimensions of (3×130×130)mm. Three standard test methods (ASTM) were used to measure the limiting oxygen index (LOI), rate of burning (RB) and maximum height of flame (H). the results showed that all of these additives exhibit sufficient flame retardants and some percentage caused non burning of the polymers under study.